Microsoft Teams and Microsoft Whiteboard – Between Reality and Opportunities - Mariya Zhelyazkova (Педагогически форум)
The article presents some of the results of a survey among teachers on distance learning platforms with focus on Microsoft Teams. Advantages and disadvantages of the platform and of the additional Microsoft Teams application, Microsoft Whiteboard – one of the five most frequently used by teachers during the distance learning, have also been assessed.